2023
DOI: 10.3389/fmicb.2023.1111087
|View full text |Cite
|
Sign up to set email alerts
|

The diversity and abundance of bacterial and fungal communities in the rhizosphere of Cathaya argyrophylla are affected by soil physicochemical properties

Abstract: Cathaya argyrophylla is an ancient Pinaceae species endemic to China that is listed on the IUCN Red List. Although C. argyrophylla is an ectomycorrhizal plant, the relationship between its rhizospheric soil microbial community and soil properties related to the natural habitat remains unknown. High-throughput sequencing of bacterial 16S rRNA genes and fungal ITS region sequences was used to survey the C. argyrophylla soil community at four natural spatially distributed points in Hunan Province, China, and func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 62 publications
1
3
0
Order By: Relevance
“…The results of this study showed that Actinobacteria, Proteobacteria, Acidobacteria, Bacteroidetes, Firmicutes, Verrucomicrobia, Planctomycetes and Chloroflexi were the dominant phyla in the microbiomes of P. lactiflora cultivars, among which the relative abundance of Actinobacteria, Proteobacteria and Acidobacteria was much higher than that of other phyla. This finding has also been confirmed in Cathaya argyrophylla and Chinese fir [48,49]. We also noted that the rhizosphere bacterial communities associated with P. lactiflora exhibited high diversity and abundance.…”
Section: Discussionsupporting
confidence: 83%
“…The results of this study showed that Actinobacteria, Proteobacteria, Acidobacteria, Bacteroidetes, Firmicutes, Verrucomicrobia, Planctomycetes and Chloroflexi were the dominant phyla in the microbiomes of P. lactiflora cultivars, among which the relative abundance of Actinobacteria, Proteobacteria and Acidobacteria was much higher than that of other phyla. This finding has also been confirmed in Cathaya argyrophylla and Chinese fir [48,49]. We also noted that the rhizosphere bacterial communities associated with P. lactiflora exhibited high diversity and abundance.…”
Section: Discussionsupporting
confidence: 83%
“…Ascomycota and Basidiomycota , the predominant fungal phyla, are present in all groups, accounting for over 90% of the microbial communities [ 187 , 207 , 208 , 209 ]. Demonstrating strong adaptability, these phyla are widely distributed across various environments, such as soil, rocks, and organic matter, thus dominating microbial communities.…”
Section: Discussionmentioning
confidence: 99%
“…Using 20 ng/μL of the DNA extracted from the rhizosphere soil of YQ1, YQ2, XQ2 and FH as PCR template. The bacterial 16s rRNA V3-V4 region specific primers (338F: 5′-ACTCCTCCTACGGGAGCAGCAGCAMUR-3′; 806R: 5′-GGACTACHVGGGTWTCTAAT-3′) were used for PCR amplification ( Xie et al, 2023 ). The reaction system was as follows: Q5 high-fidelity DNA polymerase (0.25 μL), 5 × reaction buffer (5 μL), 5 × high GC buffer (5 μL), dNTP (10 mM, 2 μL), template DNA (2 μL), forward primer (10 μM, 1 μL), reverse primer (10 μM, 1 μL) and ddH 2 O (8.75 μL).…”
Section: Methodsmentioning
confidence: 99%
“…A total of 20 ng/μL of DNA extracted from YQ1, YQ2, XQ2 and FH rhizosphere soil was also used as template for PCR amplification of fungal ITS sequence. The fungal ITS1 region primers (ITS5-1737-F: 5′-GGAAGTAAAAGTCGTAACAAGG-3′; ITS2-2043-R: 5′-GCTGCGTTCTTCATCGATGC-3′) were selected for amplification and sequencing ( Xie et al, 2023 ). The PCR reaction system was the same as the above 16S rDNA high-throughput sequencing.…”
Section: Methodsmentioning
confidence: 99%